(untitled) (Third Sector Social Economic Review, 2020)
In the current study, it was aimed to investigate the relations between phonetic awareness, writing awareness, mathematical and scientific skills of the children attending to a kindergarten in terms of structural equality modelling. The sampling of the study was made up of 100 students attending to a kindergarten in the city of Ankara. The current research is a correlational scanning study. As a data collection tool, “General Information Form”, Evaluation Tool for Preschool Writing and Vocabulary Awareness”, “Phonological Awareness Scale” and “Marmara Readiness Scale for Primary education” were used. The data was analysed using the package program of AMOS. In testing the hypotheses regarding relation in the research, path analysis technique under structural equality model was used. Depending on the results obtained in the study, it was found that there was a medium level significant relation between the phonological awareness skills and writing skills with mathematical skills while there was a low level significant relation with science skills. In addition, a significant relation was found between mathematical skills and scientific skills at a medium level. Another finding obtained in the study was that phonological awareness had a mediation effect on script awareness and mathematical skills.